Exploiting measurement-based validation for a high-fidelity model of dynamic indentation of a hyperelastic material. (15th October 2016) - Felipe-Sesé, Luis; Diaz-Garrido, Francisco A.; Patterson, Eann A.
Abstract: The high-speed (up to 1 m/s) loading and unloading of a rubber block by a rigid wedge has been simulated using a finite element model. The model has been refined and validated using measured data obtained from combined fringe projection and two-dimensional digital image correlation during the real-time loading and unloading of a rubber block by an aluminium wedge. Comprehensive data was obtained from the experiment in the spatial and temporal domains at resolutions of 0.075 mm and 0.00125 s respectively. Image decomposition techniques were used to represent the predicted and measured displacement fields in order to allow a number of quantitative measures to be employed to assess the fidelity of the model. It was demonstrated that it was essential to refine the Mooney–Rivlin material model to provide an accurate representation of the material behaviour for the speeds of the loading and unloading. The refined model was validated using the European Committee for Standardization (CEN) procedure and found to exhibit differences relative to the experiment of less than 5%. Together the predicted and measured data fields probably represent the best description yet of a soft material being deformed by a rigid indenter.